Kreativitas Siswa Slbn Gedangan Sidoarjo dalam Membuat Batik Menggunakan Canting Cap Berbahan Kertas - Supeni Saputri; Setyo Yanuartuti; Indar Sabri (Syntax Literate, 2023)
Vocational learning in SLB is prioritized learning when compared to academic learning. This is because vocational programs are considered to be more needed by SLB students regarding the independence of students if they have graduated, they are expected to have the provision of work skills and be ready to live in society. Comparison of vocational learning is 60% and 40% of academic learning. Vocational programs are educational programs that aim to prepare personnel who can define expertise and skills in their fields, are ready to work and able to compete in the world of work globally. Gedangan SLBN is a driving and referral SLB school in East Java so that it becomes a reference school for other SLB in East Java. One of the vocational programs in the Gedangan Sidoarjo SLBN is the vocational batik. In the vocational batik program, students are taught to make stamped batik using canting stamps made of paper. In this study, an analysis was carried out on the creativity of students when working on batik accompanied by the batik they produced. The method used is descriptive qualitative. In the process of making, student creativity can be seen from the changes in the results of one work with another. The difference between the results of the work and those exemplified by the teacher indicates that there is a creative thinking process carried out by students